Case Report : Acute Appendicitis - Delidios Arimbi; Jefri Jefri; Imam Fajri (Jurnal Siti Rufaidah, 2024)
Appendicitis is inflammation that occurs in the Appendix vermicularis where Appendicitis generally occurs due to an inflammatory process of bacteria. This disease is the most common acute abdominal surgical case. Appendicitis can affect all age groups, 16-year-old female patients with complaints of lower right abdominal pain since 2 days ago. The patient was diagnosed with Acute Appendicitis. The procedure is in the form of surgery, namely Appendectomy. The most common complication found in acute appendicitis is appendiceal perforation, either in the form of free perforation or perforation in the appendix which has been affected (infiltrates) in the form of a mass consisting of a collection of appendices, cecum and small intestine. If a perforation has occurred, then the possibility of peritonitis.